Acupuncture for the treatment of diarrheal-predominant irritable bowel syndrome: study protocol for a pilot randomized controlled trial - Qi, Ling-Yu (Trials, 2021)
BACKGROUND: Irritable bowel syndrome (IBS) is one of the most common functional gastrointestinal diseases. Although acupuncture has become a common alternative therapy for IBS, there is insufficient evidence for its effectiveness. This study was designed to assess the efficacy and feasibility of acupuncture in the treatment of IBS. METHODS/DESIGN: This is a multicenter randomized controlled clinical trial. According to the ratio of 1:1:1, 90 patients with irritable bowel syndrome will be randomly divided into specific acupoints (SA) group, non-specific acupoints (NSA) group, and non-acupoints (NA) group. All patients will be treated with acupuncture 12 times within 4 weeks and followed up for 8 weeks. The primary outcome is the response rate, the percentage of patients whose average value of worst abdominal pain is 30% better and the days of loose stool is 50% less than the baseline, at week 4 after randomization. The secondary outcomes include the response rates at other time points, IBS Symptom Severity Scale (IBS-SSS), Patient Health Questionnaire-9 depression scale (PHQ-9), IBS-Quality of Life scale (IBS-QOL), IBS Adequate Relief (IBS-AR), Abdominal Pain Score, Abdominal Bloating Score, Bristol Stool Score (BBS), blinding assessment, and credibility evaluation. Adverse events will be monitored and recorded during the trial. TRIAL REGISTRATION: Chictr.org.cn ChiCTR2000030670. Registered on 9 March 2020.